Formação inicial para o trabalho pedagógico com os anos iniciais do ensino fundamental: estudo do curso de Educação Física/Licenciatura/UFSM - Rodrigues, Rosenan Brum (2015)
This study aimed to investigate how to configure the initial formation in Physical Education/Bachelor of UFSM for pedagogical work at the first years of Elementary School. To do so, it was used the documentary analysis of the Education Program Course (PPC), the curriculum and programs of disciplines of Physical Education/Bachelor/UFSM and educational laws of the country and of Rio Grande do Sul state, referring to the early years of fundamental teaching fundamental and further. We applied questionnaires and semistructured interviews conducted with students from the last half of the course. The survey findings show a gap between the university and the school environment; curriculum disintegration and the absence of a compulsory subject that deals with the specificity of the pedagogical work in the early years. In this sense, a curriculum restructuring is essential, covering all levels and types of education. Specifically, it is understood that working with children in the early, it is necessary to propose a theoretical perspective that takes into account the historical and social conditions, which are the life of each person.